Research and Application of Computer Technology in the Transformation Mode of Scientific and Technological Achievements in Chinese Universities. Issue 3 (October 2020) - Guan, Xiaoxu; Deng, Ke; Qi, Qirong
Abstract: Colleges and universities are the important gathering place of high-end talents in China. Every year, colleges and universities undertake many national scientific research projects, so there will be a large number of patented technologies and scientific and technological achievements. But in the end, over 90% of these achievements were "locked away" and the achievements were not transferred, not allowed to transfer, or there was no benefit after transformation. Therefore, how to apply computer technology effectively transform and apply scientific and technological achievements in universities is of great significance to promote mass entrepreneurship and innovation. Therefore, this paper discusses the transformation mode of scientific and technological achievements in colleges and universities in China.At present, the scientific and technological achievements of foreign universities account for the mainstream of the national transformation activities while the transformation of scientific and technological achievements in China is still in its infancy. Through years of effort and based on our country launching a series of related policies that give corresponding support, encourage, guide and make unremitting efforts to innovation and exploration, we have obtained some experience in the field of transformation of scientific and technological achievements and achieved a certain economic and social benefits. Up to now, a number of universities in China have established scientific and technological achievements transformation centers, which can be seen that China attaches great importance to the transformation of scientific and technological achievements in universities. Therefore, in the current era, how to transform the scientific and technological achievements of colleges and universities into practical social application more efficiently is a problem that must be deeply studied.